MSMEs MARKETING COMMUNICATION STRATEGY IN OFFERING SERVICES THROUGH INSTAGRAM - Muhammad Yusuf; Muhammad Alfikri (KABILAH : Journal of Social Community, 2022)
Abstract: The empowerment of MSMEs in the midst of globalization and high competition causes MSMEs to need them to be ready to face difficulties around the world, such as expanding goods and administrative progress, To develop the interest of shoppers to try and buy goods sold by MSMEs, manpower is needed, various strong advertising systems, one of which is with limited time training. One of the media counting web media is virtual entertainment. This research is expected to dissect the correspondence system of MSMEs in making offers through Instagram. The adequacy of progress is estimated by the idea of AIDA (Consideration, Interests, Desires, Activities). The results of the examination revealed that the adequacy of MSME progress regarding services on Instagram media. This problem shows that progress through Instagram media is very helpful to attract customers to use MSME services.. Keywords: Communication Strategy, MSMEs, Service Services